Viewing the influence of accessibility, information technology on competitive action in small-medium micro-businesses - Audrey M Siahaan (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
This study aims to examine the effect of accessibility, information technology on competitive action in MSMEs. The independent variables in this study are accessibility and information technology. The dependent variable is competitive action. The research method used is descriptive quantitative. Sample of this research is MSMEs that register as Gojek partners in East Medan District, where Gojek partners are in the vicinity of HKBP Nommensen University and Medan State University. The sample uses the quota sampling method—the data collected by using a questionnaire distributed directly to SME traders as many as 30 questionnaires. Data analysis techniques uses multiple linear regression analysis, with hypothesis testing t-test, F test, and determination regression test. The results of this study indicate simultaneously accessibility and information technology have a positive effect on competitiveness. This is because the sample is MSMEs located around Medan State University and HKBP Nommensen University where people will come alone to their restaurants without using an application because of the close distance. We can see from the coefficient of determination that the new accessibility of information technology must be supported to influence competitive action.